PENGEMBANGAN PEGAWAI PADA UNIVERSITAS MALIKUSSALEH LHOKSEUMAWE - Dahrum .; Murniati AR; Khairuddin . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2012)
Abstract: Employee development is one of factors that influences organization productivity and can improve the quality of university. This research objective was to figure out employee development program, employee development process, and obstacles faced in employee development. This research used qualitative approach and descriptive approach. Data collection technique used was observation, interview, and documentation study. Subject of the researchwere rector, vice rector for general and finance affairs, head of general and finance administration bureau, head of personnel division, staff of personnel division, Dean, vice dean II, head of faculty administrative office, and administration staff. The result showed that: 1) employee development program was good and service procurement training, laboratory training,computer training, financial training, archive management training, and leadership training. Malikussaleh University of Lhokseumawe also gave study permit to take undergraduate and post graduate program for the employees who wanted to improve their competence. There was also a training program that is a follow-up of the ministry of national education. 2) The employeedevelopment process was through education and training, that is granting permit to the employees to take undergraduate and post graduate program, computer training, was good and service procurement training, financial training, archive management training, and leadership training, laboratory training, and also prajabatan training (a training for civil servant candidates before appointed as permanent employee). The promotion was based on the length of service, rank, and the performance of employee. Job rotation was not performed in order to make the employees become more professional in their own field and the discipline should be improved. 3) The obstacles faced in improving the competence of the employee were internal and external factor. Internal factor was the low of work motivation of the employee, the low of coordination with vertical organizations and the ministry of national education, Internal factor was there was government’s regulation that only employee with superintendent rank can take the leadership training, and there was lack of budget due to no cash injection from the vertical organization (Province, Regency, City).Keywords : Employee Development Management